Neural representations of own-voice in the human auditory cortex - Hosaka, Taishi (Sci Rep, 2021)
We have a keen sensitivity when it comes to the perception of our own voices. We can detect not only the differences between ourselves and others, but also slight modifications of our own voices. Here, we examined the neural correlates underlying such sensitive perception of one’s own voice. In the experiments, we modified the subjects’ own voices by using five types of filters. The subjects rated the similarity of the presented voices to their own. We compared BOLD (Blood Oxygen Level Dependent) signals between the voices that subjects rated as least similar to their own voice and those they rated as most similar. The contrast revealed that the bilateral superior temporal gyrus exhibited greater activities while listening to the voice least similar to their own voice and lesser activation while listening to the voice most similar to their own. Our results suggest that the superior temporal gyrus is involved in neural sharpening for the own-voice. The lesser degree of activations observed by the voices that were similar to the own-voice indicates that these areas not only respond to the differences between self and others, but also respond to the finer details of own-voices.